2020
DOI: 10.3390/pathogens9100810
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Human Rotavirus in Wuhan, China (2011–2019): Predominance of G9P[8] and Emergence of G12

Abstract: Rotaviruses are a major etiologic agent of gastroenteritis in infants and young children worldwide. To learn the shift of genotypes and genetic characteristics of Rotavirus A (RVA) causing diarrhea in children and adults, a hospital-based surveillance of rotavirus was conducted in Wuhan, China from June 2011 through May 2019, and representative virus strains were phylogenetically analyzed. Among a total of 6733 stool specimens collected from both children and adults with acute gastroenteritis, RVA was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…22 G9P [8] has been the most prevalent strain in China. 32 This was also true in this study; although the RV strain circulating in the pediatric population changed unpredictably from year to year, G9P [8] is still the most dominant single strain of RV infection among children <5 years of age in Suzhou, with certain persistence from 2013 to 2019. 33 The first emergence of G9P [8] was in the 1980s, 7 and then G9P [8] has spread worldwide, which gained predominance in several nations (eg, Thailand, Ghana, Australia, 25,34,35 as well as China 36 ).…”
Section: Discussionsupporting
confidence: 63%
“…22 G9P [8] has been the most prevalent strain in China. 32 This was also true in this study; although the RV strain circulating in the pediatric population changed unpredictably from year to year, G9P [8] is still the most dominant single strain of RV infection among children <5 years of age in Suzhou, with certain persistence from 2013 to 2019. 33 The first emergence of G9P [8] was in the 1980s, 7 and then G9P [8] has spread worldwide, which gained predominance in several nations (eg, Thailand, Ghana, Australia, 25,34,35 as well as China 36 ).…”
Section: Discussionsupporting
confidence: 63%
“…Supportively, Fukuda et al, have currently reported three strains of DS‐1‐like G9P[8] with gene constellation G9‐P[8]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2 in Thailand, containing both genogroup 1 and 2 genes 77 . Several previous studies have also detected mono‐reassortant G9P[8] strains possessing the NSP4 gene of the E2 genotype in the genetic background of Wa‐like RVA in Japan 69,78 and China, 68 which seemed to be reassorted with the NSP4 gene of E2 genotype of the G2P[4] strains. The findings of the present study also indicated that some of the I1 and E1 genotypes were in association with their corresponding VP7 and VP4 genotypes ( n = 6, G1P[8]‐I1‐E1; n = 9, G9P[8]‐I1‐E1).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of RVA in adults with diarrhea ranged from 2.8% to 17.2% according to studies from India, Russia, Germany, and other countries 6–9 . In China, RVA prevalence in adults with diarrhea has ranged from 10.9% to 30.1% 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…In China, a national surveillance network for rotavirus diarrhea is aimed at children under 5 years of age and does not include adults. Although some studies have reported RVA prevalence in adults with diarrhea in China, 19–22 genotyping and phylogenetic analysis were seldom performed, except for studies conducted in Wuhan 10,23,24 and Shanghai 11,15 . G3P[8] was the predominant strain of RVA affecting both adults and children in Wuhan from 2000 to 2006 24 .…”
Section: Introductionmentioning
confidence: 99%